2017
DOI: 10.18632/oncotarget.22685
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated atherogenesis in completely ligated common carotid artery of apolipoprotein E-deficient mice

Abstract: Complete ligation of the common carotid artery near its bifurcation induces neointimal formation due to smooth muscle cell proliferation in normolipidemic wild-type mice, but it was unknown what would happen to hyperlipidemic apolipoprotein E-deficient (Apoe-/-) mice. Examination of these mice revealed rapid development of atherosclerotic lesions in completely ligated carotid arteries within 4 weeks. Mice were fed a Western diet, starting 1 week before ligation, or a chow diet. Foam cell lesions formed as earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…2,14 In an animal experiment, we found that hyperlipidemia, which induces an inflammatory state, accelerated carotid intimal hyperplasia in Apoe −/− mice. 15 There was an increased neutrophil and CD8+ T cell adhesion and exudation, 15 supporting our finding on the association of NLR with restenosis.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…2,14 In an animal experiment, we found that hyperlipidemia, which induces an inflammatory state, accelerated carotid intimal hyperplasia in Apoe −/− mice. 15 There was an increased neutrophil and CD8+ T cell adhesion and exudation, 15 supporting our finding on the association of NLR with restenosis.…”
supporting
confidence: 80%
“…Diabetes and hyperlipidemia are known risk factors for atherosclerosis and restenosis. 14,15 Our study also found a significantly higher incidence of early ISR in diabetic patients than nondiabetic patients. 13 The proportion of diabetic patients in the high baseline NLR group (NLR ≥ 3.62) was significantly higher than that of the lower baseline NLR group (NLR < 3.62).…”
supporting
confidence: 71%
“…Several studies have shown upregulation of NOX-based NAD(P)H oxidases during the progression of AIT following flow restriction due to carotid injury (111) and lipid diet (112). The importance of intimal thickening to subclinical atherosclerosis in advancing atherosclerosis has been clearly established in ApoE gene deficient mice fed on a western diet in combination with carotid artery ligation-induced injury (113, 114).…”
Section: Subclinical Atherosclerosismentioning
confidence: 99%
“…Obesity and insulin resistance are commonly associated with hyperlipidemia and high caloric fat- enriched diets are widely accepted to induce hyperlipidemia [ 26 ]. A western-type diet (TD.88137) was chosen for these studies for its ability to induce hypercholesterolemia, obesity and atherosclerosis depending on the genetic background of the mice used for study [ 24 , 27 , 28 ]. Previous studies have shown that 16 weeks of WD regime is sufficient to induce severe hypercholesterolemia in mice [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%